2011
DOI: 10.1519/jsc.0b013e3181e7393f
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Strength and Power Recovery After Resistance Training With Different Movement Velocities

Abstract: The purpose of this study was to evaluate the time course of strength and power recovery after a single bout of strength training designed with fast and slow contraction velocities. Nineteen male subjects were randomly divided into 2 groups: the slow-velocity contraction (SV) group and the fast velocity contraction (FV) group. Resistance training protocols consisted of 5 sets of 12 repetition maximum (5 × 12RM) with 50 seconds of rest between sets and 2 minutes between exercises. Contraction velocity was contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
1
14
0
11
Order By: Relevance
“…self-paced). It has previously been reported that strength training with fast compared to slow contraction velocities caused greater exercise-induced fatigue (Ide et al, 2011). However, further research is warranted to systematically examine the eŠect of strength training contraction velocity on running performance.…”
Section: Impact Of Strength Training On Running Performance On the Samentioning
confidence: 97%
“…self-paced). It has previously been reported that strength training with fast compared to slow contraction velocities caused greater exercise-induced fatigue (Ide et al, 2011). However, further research is warranted to systematically examine the eŠect of strength training contraction velocity on running performance.…”
Section: Impact Of Strength Training On Running Performance On the Samentioning
confidence: 97%
“…Assim, testes para determinar se o IPC poderia colaborar com o resultado posterior (por exemplo: 6 horas depois da aplicação) são direções futuras de pesquisa sobre este tópico promissor, mas ainda inconclusivo. Considerando que recente revisão sistemática sobre IPC e desempenho sugere que seus efeitos mais proeminentes ocorrem em atividades glicolíticas e aeróbias 10 , futuros trabalhos poderiam avaliar melhor os efeitos do IPC em diferentes modalidades, como, por exemplo, esportes de combate [38][39][40] e exercícios resistidos [41][42][43][44] (importante contribuição glicolítica) e diferentes modalidades de dança 45 que possuem significativo grau de contribuição aeróbia, dentre outras possibilidades.…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
“…Deteriorated results obtained in this test were probably caused by incomplete recovery in the activated muscles between individual training sessions. Ide et al [22] found that dynamic muscle work during resistance training requires more time for regeneration. The authors demonstrated that the muscle could be less efficient even up to 96 hours after the training session, which has an unfavorable effect on the work during consecutive motor tasks.…”
Section: Discussionmentioning
confidence: 99%